2022
DOI: 10.3389/fphar.2021.798381
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin Alleviates Renal Fibrosis by Inhibiting RIP1-RIP3-MLKL-Mediated Necroinflammation in Unilateral Ureteral Obstruction

Abstract: Dapagliflozin, a sodium-glucose cotransporter-2 inhibitor, offers renoprotection in diabetes. However, potential for use in nondiabetic kidney disease remains unknown. Herein, we assessed whether dapagliflozin alleviates renal fibrosis by interfering with necroinflammation in a rat model of unilateral ureteral obstruction (UUO) and in vitro. After induction of UUO, rats were administered dapagliflozin daily for seven consecutive days. UUO induced significant renal tubular necrosis and overexpression of RIP1-RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 49 publications
(50 reference statements)
0
22
0
Order By: Relevance
“…This is partly due to the lack of effective drugs. DN as an important cause of CKD, and some drugs treated with diabetes like SGLT2 inhibitors have shown renal protective effects ( Sharma et al, 2017 ; Kelly et al, 2019 ), as a typical drug of SGLT2 inhibitors, dapagliflozin’s renal protective effects on CKD have been demonstrated in patients with and without diabetes ( Kurata and Nangaku, 2022 ) , and it has also displayed antirenal fibrosis activities in animal models induced by unilateral ureter obstruction and alcohol damage ( Wu et al, 2021 ; Xuan et al, 2021 ; Liu et al, 2022 ). In this study, we extended this model to the setting of renal fibrosis induced by a 0.2% adenine diet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is partly due to the lack of effective drugs. DN as an important cause of CKD, and some drugs treated with diabetes like SGLT2 inhibitors have shown renal protective effects ( Sharma et al, 2017 ; Kelly et al, 2019 ), as a typical drug of SGLT2 inhibitors, dapagliflozin’s renal protective effects on CKD have been demonstrated in patients with and without diabetes ( Kurata and Nangaku, 2022 ) , and it has also displayed antirenal fibrosis activities in animal models induced by unilateral ureter obstruction and alcohol damage ( Wu et al, 2021 ; Xuan et al, 2021 ; Liu et al, 2022 ). In this study, we extended this model to the setting of renal fibrosis induced by a 0.2% adenine diet.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and oxidative stress were critical aspects of renal fibrosis ( Meng et al, 2014 ; Rayego-Mateos and Valdivielso, 2020 ). Dapagliflozin reduces inflammation and oxidative stress in the kidneys in UUO animal models ( Xuan et al, 2021 ; Liu et al, 2022 ). Our study also showed that dapagliflozin increased content of GSH, improved activity of SOD, and decreased the content of MDA in 0.2% adenine diet-fed mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the conditions of unilateral ureteral obstruction and renal ischemia/reperfusion injury, tubular necroptosis is markedly upregulated, which in turn promotes NOD-like receptor protein 3 (NLRP3) inflammasome activation leading to renal fibrosis. Whereas genetic or pharmacologic inhibition of the necroptosis axis prevented activation of necroinflammation and subsequent development of renal fibrogenesis ( Chen et al, 2018 ; Jiang et al, 2022 ; Xuan et al, 2022 ), implying a relationship between necroinflammation and renal fibrosis. Most importantly, in the CP-induced AKI model, Landau et al (2019) found that continuous activation of regulated necrosis following CP treatment was shown to be the most important factor that drives the transition and progression of AKI to chronic irreparable kidney disease.…”
Section: Necroptosis In Cp-induced Acute Kidney Injury (Aki)mentioning
confidence: 99%